Life trajectory in percussive music and education integrated to the Dona Zefinha Group (Research, Society and Development, 2022)
This text reflects on the relationship between percussive music and education through the presentation and analysis of the biography of an artist-teacher (pedagogue) percussionist and drummer, member of the sceno-musical group Dona Zefinha (Itapipoca, Ceará, Brazil). The methodological path of this study is guided by the experiential approach that provides the perception of self-knowledge, while expanding the creation of self-referenced knowledge, in a continuous movement of self-training, related to the sociocultural context in which the subject enters. With all the analyzes carried out on the aforementioned artistic-educational trajectory of the author of this text, it is concluded that the perspective of self-education based on the autobiographical bias, potentiated the professional performance of the subject in focus, which emerged and perfected together with everyday artistic and educational practices, as a constitutive condition of the performance itself; a reflective process that developed in practice and also on it.